Spontaneous Subcapsular Renal Hematoma as Cause of Hypovolemic Shock in a Chronic Hemodialysis Patient - Jorge Luis Bermudez-Gonzalez; Bethsabel Rodríguez-Encinas; Ángel Miguel Beverido-Florido; Jesús Alejandro Gabutti-Thomas (Case Reports in Radiology)
Subcapsular renal hematomas may appear spontaneously in patients in chronic hemodialysis, though other causes as neoplasms, vasculitis, and infections should be excluded. Patients may present with abdominal pain and hemorrhagic shock; hence, early diagnosis is vital. Nephrectomy or renal artery embolization are suitable treatment options.